From eight-membered 10π electron sulfur-nitrogen cycles to bicycles and cages: a theoretical approach - Gleiter, Rolf; Haberhauer, Gebhard; Woitschetzki, Sascha (Chemistry - a European journal, 2014)
Abstract A simple way of rationalizing the structures of cyclic, bicyclic, and tricyclic sulfur?nitrogen species and their congeners is presented. Starting from a planar tetrasulfur tetranitride with 12π electrons, we formally derived on paper a number of heterocyclic eight-membered 10π electron species by reacting the 3p orbitals of two opposite sulfur centers with one radical each, or by replacing these centers by other atoms with five (P) or four (Si, C) valence electrons. This led to planar aromatic 10π electron systems, nonplanar bicyclic structures with a transannular S?S bond, and tricyclic structures by bridging the planar rings with an acceptor or donor unit. The final structures depend on the number of π electrons in the bridges. Intermediate biradicals are stabilized by Jahn?Teller distortion, giving transannular S?S bonds between the NSN units. This procedure may be summarized by two rules, which provide a rationale for the structures of a large number of sulfur?nitrogen-based molecules. The long bonds between the NSN units show a p character of >95?%. The qualitative results have been compared with known molecular structures and the results of B3LYP/cc-pVTZ calculations as well as CASSCF and CASVB calculations. B3LYP/cc-pVTZ calculations have also provided the UV/Vis spectra and the NICS values of the planar 10π systems.
Gesehen am 13.07.2020